Harnessing Epistemology with Consumer Decision-Making and Marketing Strategy - Ajayi, Toluwalase (NIU Journal of Social Sciences, 2025)
The article advocates for an epistemological framework regarding consumer choices and marketing tactics. Consumer behavior, particularly in relation to selecting products from various alternatives, poses several questions: Why do individuals engage in shopping? Why do they opt for specific items among numerous options? How is it that a particular product becomes the preferred choice for certain consumers and consumer segments? How can marketers create a portfolio for such a product, considering the range of diverse consumers/customers? Given that the consumer process of making purchasing decisions is increasingly intricate. The reality is that every company makes choices grounded in its understanding. However, how does an organization determine what it knows? This inquiry is crucial since a company's insights influence its decisions, strategies, and activities. In the realm of philosophy, the examination of knowledge is termed epistemology; it explores the origins of knowledge, how we validate its accuracy, and how we apply it. Nowadays, businesses possess more data than at any time in history, thanks to technology and data. However, possessing a wealth of information doesn’t necessarily equate to having substantial knowledge.  The paper argues that Sensory analysis is an essential collection of techniques for gaining research and marketing insight into product consistency and variability. Although these sensory evaluations are straightforward and easy to implement; others are more intricate and necessitate training and expertise. Keywords : Epistemology, Consumer, Ideas, Perception, Primary qualities, Secondary qualities.